Peran Guru PAI dalam Membentuk Karakter Peserta Didik di SMK NU Darussalam Kecamatan Srono - Slamet Slamet; Mulajimatul Fitria; Vaesol Wahyu Eka Irawan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the role of PAI teachers in improving students' character and the supporting and inhibiting factors for students at SMK NU Darussalam, Srono District. The research method used in this research is qualitative. This research used observation, interview, and documentation techniques to collect data. In this research, there are two data sources used, namely primary and secondary data sources. The data analysis technique used is interactive analysis consisting of data reduction, data presentation, and concluding. The research results show that the role of PAI teachers at SMK NU Darussalam, Srono District, positively impacts student character formation. Supporting factors include a supportive family environment, facilitating educational institutions, a positive community environment, and supportive technological media. On the other hand, inhibiting factors include an unstable family environment, negative school culture, negative peer influence, and the negative impact of technological media.